Heritability of Atrial Fibrillation - Weng, Lu-Chen; Choi, Seung Hoan; Klarin, Derek; Smith, J Gustav; Loh, Po-Ru; Chaffin, Mark; Roselli, Carolina; Hulme, Olivia L; Lunetta, Kathryn L; Dupuis, Josée; Benjamin, Emelia J; Newton-Cheh, Christopher; et al. (Circulation. Cardiovascular genetics, 2017)
Previous reports have implicated multiple genetic loci associated with AF, but the contributions of genome-wide variation to AF susceptibility have not been quantified. We assessed the contribution of genome-wide single-nucleotide polymorphism variation to AF risk (single-nucleotide polymorphism heritability, ) using data from 120 286 unrelated individuals of European ancestry (2987 with AF) in the population-based UK Biobank. We ascertained AF based on self-report, medical record billing codes, procedure codes, and death records. We estimated using a variance components method with variants having a minor allele frequency ≥1%. We evaluated in age, sex, and genomic strata of interest. The for AF was 22.1% (95% confidence interval, 15.6%-28.5%) and was similar for early- versus older-onset AF (≤65 versus >65 years of age), as well as for men and women. The proportion of AF variance explained by genetic variation was mainly accounted for by common (minor allele frequency, ≥5%) variants (20.4%; 95% confidence interval, 15.1%-25.6%). Only 6.4% (95% confidence interval, 5.1%-7.7%) of AF variance was attributed to variation within known AF susceptibility, cardiac arrhythmia, and cardiomyopathy gene regions. Genetic variation contributes substantially to AF risk. The risk for AF conferred by genomic variation is similar to that observed for several other cardiovascular diseases. Established AF loci only explain a moderate proportion of disease risk, suggesting that further genetic discovery, with an emphasis on common variation, is warranted to understand the causal genetic basis of AF.